Effects of autologous dental pulp stem cells and mineral trioxide aggregate on exposed dogs’ dental pulp - Dalia K. Hemdan; Manar A. Selim; Rania A. Galhom; Mohamed H. El Daharawy; Hayam Y. Hassan (Journal of Oral Biology and Craniofacial Research)
This study evaluated exposed dogs’ dental pulp response after direct capping with autologous dental pulp stem cells (DPSCs) and compared the results with MTA (Angelus, Brazil). Sixty teeth from six mongrel dogs were included (n = 60), allocated into four groups; negative control (n = 6), positive control (n = 6), MTA (n = 24), and DPSCs (n = 24). DPSCs were isolated and cultured from extracted first premolars (1premolar/dog). The teeth were prepared for histological and immunohistochemical analyses. Statistical analysis was calculated using ANOVA tests, P ≤ 0.05. MTA induced the formation of an almost complete calcific bridge. DPSCs successfully regenerated the injured pulp and dentin. The comparison between the capping groups and time intervals had a statistically significant effect, as well as, the interaction between the two variables. DPSCs had greater ability in the reparative and regenerative process of dentin and odontoblastic differentiation by having a significantly stronger TGFβ1 expression than MTA.